2020
DOI: 10.1155/2020/8016791
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity among Recipients of Antiretroviral Therapy at HIV Clinics in Gaborone, Botswana: Factors Associated with Change in Body Mass Index

Abstract: Background. Factors associated with overweight/obesity among antiretroviral therapy (ART) recipients have not been sufficiently studied in Botswana. Objectives. To: (i) estimate the prevalence and trends in overweight/obesity by duration of exposure to ART among recipients, (ii) assess changes in BMI categories among ART recipients between their first clinic visit (BMI-1) and their last clinic visit (BMI-2), (iii) identify ART regimen that predicts overweight/obesity better than the others and factors associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
(33 reference statements)
1
10
1
Order By: Relevance
“…The current study found a high (39%) prevalence of overall overweight/obesity, and the prevalence was higher in women than in men. The association observed between gender and overweight/obesity has been previously documented [39][40][41]. The study established that age was also a factor associated with overweight.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The current study found a high (39%) prevalence of overall overweight/obesity, and the prevalence was higher in women than in men. The association observed between gender and overweight/obesity has been previously documented [39][40][41]. The study established that age was also a factor associated with overweight.…”
Section: Discussionsupporting
confidence: 58%
“…The difference could be attributed to the difference in the duration of ART; the Limpopo study selected participants who had been on ART for a longer duration (range: 1-121 months), whereas the current study was conducted among patients recently initiated on ART. This further explains the slightly higher prevalence of overweight (29%) and obesity (17%) reported in a 12-year retrospective study of HIV patients on ART in Botswana [40].…”
Section: Discussionmentioning
confidence: 89%
“…There is a large variation in obesity prevalence in HIV infected population, with as high as 16.6% in Botswana to 17.5% in United States have been seen. 40 , 41 Studies from SSA, France and Brazil show prevalence of 2% to 13.1%. 13 , 15 , 32 , 35 , 36 , 42–44 The studies were done in different countries on different population groups with different prevalence of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…However, factors specific to HIV infection and treatment regimens have also been implicated in influencing the vulnerability of people living with HIV to increased obesity [ 43 ]. Despite the growing number of studies reporting obesity in women with HIV in the general population [ 3 , 5 , 44 , 45 ], there are limited data on GWG trends in this group. One South African study reported that women with HIV experience greater inadequate GWG [ 39 ], however, we found high prevalence of excessive GWG in our cohort.…”
Section: Discussionmentioning
confidence: 99%